(untitled) (Jurnal Komunikasi Pembangunan, 2016)
Risk communication is physical and mental conditions that underlie the management of information in facing risks of a disaster. This study is aimed to describe risk communication strategies conducted by a community in Mount Merapi, a disaster-prone area. The study will also analyze the framing that underlies the community’s resistance towards government relocation policy. This research is expected to contribute to the development of appropriate risk communication strategies in disasters management, for both government and local communities. This Research uses qualitative methods and strengthen by quantitative data with purposive sampling. This study states that there are four framing elements underlying the peoples resistance. First, the relocation policy is considered to be disregardful of the peoples rights for proper settlement. Second, the justification of the matter is the government unjustness. Third, is more of a moral reason underlying the peoples resistance towards the policy which is an effort to retaining personal welfare and sustaining homeland. The fourth framing element, are recommendations for action, the people have decided to stay inthe village and improve preparedness and economic self-reliance. The decision to survive living in a disaster prone area is increasingly raising the peoples awareness of the importance of risk communicationin facing the threats of possible disasters. Keywords : disaster, relocation, framing, risk communication